Clinical profile and outcomes of modified internal limiting membrane peeling technique in patients with large macular hole - Amit S. Nene; Sheetal Divate; Onkar H. Pirdankar; Pushpanjali Badole; Pratik Shenoy; Smitesh Shah (Journal of Clinical Ophthalmology and Research)
Aim: The aim of this study was to assess the clinical profile and outcomes of the modified internal limiting membrane (ILM) peeling technique in patients with large macular holes (MHs) (400 μm). Methods: It is a retrospective case series where patients who underwent MH repair surgery by modified ILM peeling technique between January 2023 and June 2023 were considered. Subjects with MH minimum diameter >400 μ were included whereas subjects with associated retinal comorbidities such as diabetic retinopathy, retinal detachment, macular dystrophies, retinal degeneration, and cases with missing data were excluded. All surgeries were performed by a single surgeon. Various MH indices such as macular (MHI) and tractional hole index (THI) and diameter hole index were calculated and their association with postoperative best-corrected visual acuity (BCVA) was analyzed. Results: Eleven eyes of 11 patients with mean ± standard deviation age 66.36 ± 10.17 were included. Paired t-test revealed statistically significant improvement in post-BCVA (P = 0.006). Pearson correlation revealed a significant positive correlation between minimum diameter and postoperative BCVA (r = 0.76, P = 0.007) suggesting larger diameters were associated with poor visual acuity. MH inner diameter also showed a significant moderate positive correlation with postoperative BCVA (r = 0.61, P = 0.04). Furthermore, macular hole index and THI showed significant moderate (r = −0.68, P = 0.02) and strong (r = −0.82, P = 0.002) negative associations with postoperative BCVA, respectively, suggesting an increase in macular and THI associated with an improvement in postoperative BCVA. Conclusion: Managing larger MHs is challenging due to poor visual prognosis and lower anatomical success rate. The modified ILM peeling technique in our case series demonstrated improved anatomical and visual outcomes; however, prospective comparative study would give better insight.